The Interpretation of Islamic Education: Perceptions of Modernist and Classical Thinkers on The Qur’anic Exegesis - Yusuf Olawale Uthman Owa-Onire (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2022)
This article discussed the perceptions of Muslim thinkers on the Quran and tafsir in terms of both the classic and modern eras. However, the article is subjected to the analytical comparison between the classical and modern eras of Qur’anic exegesis. Throughout the research about these thoughts, the root-age of tafsir with the approach of the interpreters and the Islamic thinkers will gain special attention. To establish adequate information in the study, a clear picture of the exegetical thoughts with the several perceptions of classical and modernist thinkers is drawn accordingly. However, in enabling this projected idea to reach the target area, the research adopted the following analytical method, reviewing the available literature; such as books, articles, journals, and the dissertation, which may have a direct or indirect connection to this research. Nevertheless, the noble Qur’an is quite recognized as a book representing the first source of evidence in Islam; many perceptions may be established in the course of striving to gain its exegetical expression. So, this article has drawn a straight line to reach the efforts of Muslim thinkers in both the late and current era to protect the sacred book (Qur’an) with their noble knowledge of Qur’anic exegesis.